EFEKTIVITAS PENERAPAN MODEL MIND MAPPING BERBANTUAN MEDIA PUZZLE TERHADAP PENINGKATAN PEMAHAMAN KONSEP SISWA KELAS V - Yunia Filiyanda; Fina Fakhriyah; Ika Ari Pratiwi (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2024)
The aim of this research is to determine the effectiveness of the mind mapping model assisted by puzzle media in helping fifth grade students understand the science concept. This research uses a quantitative experimental design, namely one group pretest-posttest. The research population consisted of 17 fifth grade students, and the sampling method used was saturated sampling. Data was collected through tests, observations, interviews and documentation. Data were evaluated by t-test. Based on research findings, the use of the Mind Mapping model with Puzzle media can increase 5th grade elementary school students' knowledge regarding science content ideas using the paired sample t test. The findings show that the calculated t value is -9.535, with a sig value of 0.00. The assessment sig value (2-tailed) is 0.00, which is smaller than the significance criterion of 0.05. Therefore, Ha is accepted and Ho is rejected. It can be said that the Mind Mapping method and Puzzle media can help students understand concepts better. Keywords: Mind Mapping Model, Concept Understanding, Puzzle Media